Herpes Zooster Induced Diabetic Ketoacidosis - Suwita, Christopher Surya; Johan, Michael; Tahapary, Dicky L.; Darmowidjojo, Budiman (Jurnal Penyakit Dalam Indonesia, 2018)
Diabetic ketoacidosis (DKA) is an acute, life-threatening complication of diabetes which is common in daily practice. DKA is the result of severe insulin deficiency and often presents as the first symptom of an undiagnosed diabetes even though it may also appear in individuals with diabetes. Some conditions that can trigger DKA include infections, myocardial infarction, stroke, pancreatitis, trauma, or poor treatment compliance. Skin tissue infections such as herpes zoster are rare inciting factor in DKA. This article will discuss a case of DKA that is triggered by herpes zoster.